A Postcolonial Insight into African Onomastics in Europhone Translation: A study of D. O. Fagunwa’s Selected Yoruba Narrative Names - Damola E. Adeyefa (Yoruba Studies Review, 2022)
Most African names have sociocultural identities, which convey thoughts, traditions, fortunes, conditions, histories, and other features. Translating African indigenous names from Yoruba into French and English transcends Saussure’s postulation of signified–signifier arbitrariness (Saussure,1975). Previous studies in African onomastic translation have concentrated mostly on Europhone translation, with insufficient scholarly attention paid to the Yoruba-French onomastic translation.  Therefore, this work explores Yoruba names in a literary onomastic translation with a view to bringing to fore the connotative embodiments of African names. Establishing techniques to employ in translating African names into European languages like French and English. The study adapts Newmark (1988) and Moya (2000) approaches to name translation. The content analysis was employed in the investigation and interpretation of the data that were purposively selected from two D. O. Fagunwa’s Yoruba novels – Ògbójú Ọdẹ nínú Igbó Irúnmalẹ̀ (2005) and Ìrèké-Oníbùdó (2005) –and their French translations – Le preux chasseur dans la forêt infestée de démons (1989) and La fortune sourit aux audacieux(1989) – by Olaoye Abioye respectively; as well as Louis Camara’s, an Ivorian francophone, translation of Soyinka’s translation The Forest of a Thousand Daemons (1982); originally from Fagunwa’s Ogboju into French-- La Forêt aux Mille Demons (2010). The essay concludes that African names are embedded in ethnolinguistic and sociocultural connotations and specific translational techniques are imperative to their translations into European languages such as French and English